Multi-pole system analysis (MPSA) – A systematic method towards techno-economic optimal system design. (1st May 2016) - Holl, Mario; Pelz, Peter F.
Highlights: A general method (MPSA) for holistic system modeling is presented. MPSA method is able to analyze systems techno-economically. The method is applied to an exemplary application. Differences in energetic and techno-economic optimal systems are discussed. Only a techno-economic approach leads to reasonable system design and operation. Abstract: A new and general method for holistic system modeling using multi-pole formalism is presented. The motivation of our research is to develop a structured method for simultaneous system description and assessment with respect to several criteria, e.g. economic profitability, energetic efficiency and environmental impact. The method is named multi-pole system analysis (MPSA) and allows to combine an arbitrarily complex connected system. Thus, one ends up with a simple mathematical expression which generates a concentrated and broad system understanding and highlights interactions of multiple input and output quantities. The MPSA method is used to describe a conceptual wind-energy converter both energetically and economically. The resulting techno-economic analysis consists of the three essential steps of (i) techno-economic modeling, (ii) detailed energetic and economic analysis and (iii) system optimization. By applying these steps one obtains systematically and in a structured manner the techno-economic optimal system. The energetic analysis is performed by applying axiomatic conversion laws on a presented physical model of the energy conversion system. By using empiric scaling laws not only one but a multitude of possible systems are considered. The economic analysis is performed by applying economic models of the dynamic investment analysis. The techno-economic optimal system in the classic definition of Pareto optimality is shown. The method shows that only a simultaneous consideration of energetic and economic aspects leads to reasonable system design and operation.